The Complete Guide to the Herschel Objects : Sir William Herschel's Star Clusters, Nebulae and Galaxies - Bratton, Mark, 1955- (Cambridge University Press, 2011)
Provides a complete re-examination of Herschel's entire catalogue; a must-have for amateur astronomers seeking new and exciting observing challenges.
Title from publishers bibliographic system (viewed 22 Dec 2011).
Available through Cambridge books online SHEDL trial from 9th January 2012 to 9th July 2012.
Keywords: Astronomy -- Observers' manuals.; Stars -- Clusters -- Observers' manuals.; Nebulae -- Observers' manuals.; Étoiles -- Amas -- Manuels d'observation.; Nébuleuses -- Manuels d'observation.; SCIENCE -- Astronomy.; NATURE -- Sky Observation.; Astronomy; Nebulae; Stars -- Clusters; Handbooks and manuals